2022
DOI: 10.3390/microorganisms10122352
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Propionate Metabolism in Bacillus subtilis during 3-Indolacetic Production

Abstract: The genera Bacillus belongs to the group of microorganisms that are known as plant growth-promoting bacteria, their metabolism has evolved to produce molecules that benefit the growth of the plant, and the production of 3-indole acetic acid (IAA) is part of its secondary metabolism. In this work, Bacillus subtilis was cultivated in a bioreactor to produce IAA using propionate and glucose as carbon sources in an M9-modified media; in both cases, tryptophan was added as a co-substrate. The yield of IAA using pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Moreover, the viable cells of strain PE7 in the broth culture might also partially involve in growth promotion of tomato plants because our in vitro IAA and ammonia assays revealed that strain PE7 possessed the capacity to produce IAA and ammonia. Bacterial IAA plays a major role in root stimulation, cell division and enlargement, and enhances root development including root elongation and abundant formation of root hairs, thereby improving water and nutrient acquisition by plant root (Bessai et al, 2022;Castillo-Alfonso et al, 2022). In addition, ammonia released by PGPB induces a direct stimulation of plant growth through nitrogen accumulation for shoot and root growth, and biomass production (Kouam et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the viable cells of strain PE7 in the broth culture might also partially involve in growth promotion of tomato plants because our in vitro IAA and ammonia assays revealed that strain PE7 possessed the capacity to produce IAA and ammonia. Bacterial IAA plays a major role in root stimulation, cell division and enlargement, and enhances root development including root elongation and abundant formation of root hairs, thereby improving water and nutrient acquisition by plant root (Bessai et al, 2022;Castillo-Alfonso et al, 2022). In addition, ammonia released by PGPB induces a direct stimulation of plant growth through nitrogen accumulation for shoot and root growth, and biomass production (Kouam et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In the 1-21-day period (budding stage), the average growth rate of LAI for each treatment in 2021 and 2022 was 0.02-0.09 d −1 , while in the 22-49-day period (budding stage to flowering stage), the corresponding value was 0.02-0.05 d −1 . Compared with B0, M increased the average growth rate of LAI during the 1-21-day period by 64 This study then analyzed the LAI on the 49th day after the first irrigation. Significant effects were exerted by irrigation water type and the B. subtilis amounts on LAI in the saline soil (p < 0.01).…”
Section: Leaf Area Index Of Cottonmentioning
confidence: 99%
“…This is a key reason explaining the inhibition of crop growth in saline soil. In order to address the effects of saline stress, the promotion of crop growth by B. subtilis is twofold [63,64]. Firstly, B. subtilis can alleviate the adverse effects of soil water and salt stress on crops.…”
Section: Effects Of B Subtilis Amount On Soil Water and Salt Conditio...mentioning
confidence: 99%